2014
DOI: 10.3389/fnhum.2014.00067
|View full text |Cite
|
Sign up to set email alerts
|

Scale and pattern of atrophy in the chronic stages of moderate-severe TBI

Abstract: Background: Moderate-severe traumatic brain injury (TBI) is increasingly being understood as a progressive disorder, with growing evidence of reduced brain volume and white matter (WM) integrity as well as lesion expansion in the chronic phases of injury. The scale of these losses has yet to be investigated, and pattern of change across structures has received limited attention.Objectives: (1) To measure the percentage of patients in our TBI sample showing atrophy from 5 to 20 months post-injury in the whole b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
90
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(119 citation statements)
references
References 56 publications
14
90
0
6
Order By: Relevance
“…Rather, demyelination and delayed atrophy of white matter tracts develops for over one year post-TBI in rodents [30–33] and progresses for decades in TBI patients [34, 35]. This temporal pattern of delayed white matter injury may therefore provide an amendable therapeutic window; however, the mechanisms that occur between the initial traumatic event and the manifestation of white matter loss remain poorly defined.…”
Section: Chronic Neurodegeneration After Tbi: Is White Matter Injumentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, demyelination and delayed atrophy of white matter tracts develops for over one year post-TBI in rodents [30–33] and progresses for decades in TBI patients [34, 35]. This temporal pattern of delayed white matter injury may therefore provide an amendable therapeutic window; however, the mechanisms that occur between the initial traumatic event and the manifestation of white matter loss remain poorly defined.…”
Section: Chronic Neurodegeneration After Tbi: Is White Matter Injumentioning
confidence: 99%
“…The corpus callosum is particularly susceptible to injury due to a rigid attachment to the falx cerebri, a fold of dura mater that descends into the longitudinal fissure, and due to connections with the two independently mobile cerebral hemispheres [21]. A separate study determined that 96% of moderate-severe TBI patients showed atrophy of at least one brain region and 76.8% of TBI patients showed significant loss of corpus callosum volume [34]. Although the mechanisms remain poorly defined, white matter degradation, including a 25% reduction in corpus callosum thickness, was correlated with inflammatory activation at one-year after a single TBI [37].…”
Section: Damage Associated Molecular Patterns (Damps): Mediators Omentioning
confidence: 99%
“…Cancer studies have shown that therapeutic doses of irradiation can cause neurotoxic effects – especially affecting hippocampal neurogenesis, cell proliferation, differentiation and apoptosis (Dietrich et al, 2008; Monje, 2008). Stroke or traumatic brain injuries generally produce more widespread and diffuse cerebral pathologies (Bramlett and Dietrich, 2004), although hippocampal atrophy is a common finding in human survivors of traumatic brain injury (Ariza et al, 2006; Green et al, 2014; Tomaiuolo et al, 2004). The injury model used in the present study (fimbria-fornix transection) is a focal mechanical injury specifically targeting hippocampal functioning.…”
Section: Discussionmentioning
confidence: 99%
“…However, it takes weeks for stabilization of the frontal pathology to emerge as encephalomalacia, focal atrophy and loss of parenchyma. Longitudinal studies in those with TBI have shown that it takes a minimum of 6 weeks for prominent encephalomalacia consistently to be apparent in imaging studies (Blatter et al 1995), with dynamic changes in lesion size, volume and regional atrophy extending across the first year to even longer timeframes post-injury (Farbota et al 2012;Green et al 2014;Ng et al 2008). As visualized in Fig.…”
Section: Applying Structural Image Analysis Tools In Neuropsychologymentioning
confidence: 99%
“…Nonetheless, an enduring marker of global atrophy is a derivative of the Evans' index or ratio -the ventricle-to-brain ratio (VBR) where total ventricular volume is divided by brain volume and multiplied by 100 so that whole numbers are used in the quantification metric. The VBR is not only an established measure of overall brain integrity, but as a ratio it automatically adjusts (partially) for head size variation (Mathalon et al 1993) and commonly relates to neuropsychological status Green et al 2014;Olesen et al 2011;Tate et al 2011). Like all quantitative image techniques it is not without its drawbacks and there are circumstances where it may be best to adjust or correct for head size statistically (e.g., regression or covariance) rather than using a ratio like the VBR (Arndt et al (Arndt et al 1991).…”
Section: Overview Of Structural Neuroimaging Analysesmentioning
confidence: 99%